Will the Ripples Collide? A Critical Look at the Impact of External Quality Assurance Process on an English Language School - Reynolds, Seren Başor (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2014)
In recent years, in order to better cope with the increasing number of higher education institutions in the region and thus, the inevitable competition, the validation of their programs by an external/international accreditation body has become the primary objective for some universities in North Cyprus. The Eastern Mediterranean University (EMU) is not an exception to this movement. This research aims to discover the perceived impact of external quality assurance process (run by Pearson Edexcel Assured) on the development of certain pre-defined internal quality management and assurance strategies which are maintained to reinforce organizational learning within the specific context of the English Preparatory School at Eastern Mediterranean University (EMU EPS). To this end, the study focused its specific attention on the perceived impact of Pearson Edexcel Assured accreditation process on the development of core strategic building blocks of a ‘learning organization’ (i.e., ‘clarity of purpose and mission’, ‘shared leadership and involvement’, ‘experimentation’, ‘effective transfer of knowledge’ and ‘teamwork and group problem-solving’) at EMU EPS. Adopting a descriptive case study design, the study aimed to gather both quantitative and qualitative data from three different groups of internal stakeholders: the Leadership team, the EPS teachers who were directly involved in the accreditation process, and the EPS teachers who were not directly involved in the process, by means of a survey and semi-structured interviews. In addition, publicized documentation such as policies and procedures, or documents produced by the Continuing Professional Development working group, which were located on the school premises and the school’s official online communication portal, was used as supplementary qualitative data in order to support the discussions drawn from the data gathered from the participants. For the data analysis, a number of methods were used depending on the sort of the data gathered. The quantitative data were analysed by means of descriptive statistics. For the qualitative data, content analyses were conducted following the guidelines provided by Berg (2001). In this respect, a combination of deductive and inductive reasoning was applied, and the data were thematically coded into categories of emerging patterns of the participants’ views on the core components of a learning organization and the impact of the accreditation process on these attributes. The findings yielded interesting results indicating differences in the perceptions of the internal stakeholders not only as regards the degree of formative impact of Pearson Edexcel Assured accreditation process, but also regarding certain internal quality management and assurance practices such as professional development initiatives. Therefore, it is hoped that the results will serve for a better understanding of the continuing professional development initiatives in the ELT world by providing well-grounded impetus for further in-depth studies. Keywords: Accreditation, academic quality management and assurance, learning organizations, English language teaching.

ÖZ : Son yıllarda Kuzey Kıbrıs’ta faaliyet gösteren yüksek öğrenim kurumlarındaki sayısal artış ve dolayısıyla artan rekabet nedeniyle, programlarının iç ve dış denetim kurumları tarafından akredite edilmesi bu kurumların bazıları için birincil hedef haline dönüşmüştür. Doğu Akdeniz Üniversitesi (DAÜ) de bu kurumlardan biridir. Bu çalışma, Doğu Akdeniz Üniversitesi İngilizce Hazırlık Okulu (DAÜ İHO)’nda, kurumdışı bir organizasyon (Pearson Edexcel Assured) tarafından yürütülen kalite güvence sürecinin, söz konusu okulda kurumsal öğrenmenin gerçekleşmesi yönünde önceden tanımlanmış kurumsal kalite ve güvence stratejilerinin gelişimine olan algısal etkisini araştırmayı hedeflemektedir. Bu amaçla çalışma, DAÜ İHO’da Pearson Edexcel Assured tarafından yürütülen akreditasyon sürecinin, ‘öğrenen örgüt’ü oluşturan temel stratejik yapıtaşlarını (yani, ‘amaç ve misyonun netliği’, ‘paylaşımcı liderlik ve katılım’, ‘deneyimleme’, ‘etkili bilgi transferi’ ve ‘takım çalışması ve grupsal problem çözümlemesi’ni) geliştirmedeki etkisinin, söz konusu kurumda nasıl algılandığı konusuna odaklanmıştır. Betimleyici bir durum çalışması olan bu çalışmada nirengi yöntemi baz alınarak, üç ayrı grup (okul yönetimi, akreditasyon sürecinde aktif rol alan öğretim elemanları ve akreditasyon sürecinde aktif rol almayan öğretim elemanları) ile gerçekleştirilen anket ve yüzyüze görüşmelerle, hem niceliksel hem de niteliksel veri toplanmıştır. Anket ve görüşmelere ek olarak, gerek okul içinde Sürekli Mesleki Gelişim Çalışma Grubu’nun ürettiği, gerekse okulun resmi iletişim aracı olarak kullanılan portalda yer alan dökümanlar da, katılımcılardan elde edilen veriyi destekleyici nitelikte kullanılmıştır. Çalışmada toplanılan verinin niteliğine bağlı olarak farklı veri analizi metodlarına başvurulmştur. Bu bağlamda, toplanılan niceliksel veriler betimsel istatistik yolu ile analiz edilmiştir. Elde edilen niteliksel veriler ise Berg’in (2001) sunduğu esaslar ışığında yapılan içerik çözümleme yöntemi ile incelenmiştir. Bu şekilde, çalışmada yer alan grupların, öğrenen bir örgütü oluşturan yapıtaşları ve akreditasyon sürecinin bu yapıtaşları üzerindeki etkisi konusunda dile getirdikleri görüş ve yorumlarını kapsayan niteliksel veriler, hem tümdengelim hem de tümevarım muhakeme yöntemleri kullanılarak tematik olarak düzenlenip kategorilere ayrılmıştır. Bulgular, hem Pearson Edexcel Assured akreditasyon sürecinin okul üzerindeki gelişimsel etkisi hem de mesleki gelişim gibi okul bünyesi içinde başvurulan kalite yönetimi ve güvencesine yönelik çalışmalar konusunda, çalışmaya katkı koyan okul paydaşları arasında görüş farklılıkları olduğu yönünde düşündürücü ve aynı zamanda konu ile ilgili farklı çalışmalar geliştirilmesine yön verebilecek nitelikte sonuçlar ortaya koymuştur. Anahtar Kelimeler: Akreditasyon, akademik kalite yönetimi ve güvencesi, öğrenen örgüt, İngilizce dil eğitimi
Master of Arts in English Language Teaching (ELT). Thesis (M.A.)--Eastern Mediterranean University, Faculty of Education, Dept. of English Language Teaching, 2014. Supervisor: Prof. Dr. Ülker Vancı Osam.
Keywords: English Language Teaching (ELT); English Language - Study and Teaching; Quality Assurance - Accreditation - English Language, Study and Teaching - Eastern Mediterranean University - Famagusta (Cyprus, North); Accreditation; academic quality management and assurance; learning organizations